Lifecare: AI-Powered Healthcare Web App for Smarter Medical Services - Uttarwar, Yash; Manwar, Aniket; Sontakke, Badrinath; Nimbalwar, Sarvesh; Kharat, I.I; Walchale, P.M. (International Journal of Computer Sciences and Engineering, 2025)
LifeCare is a cutting-edge AI-powered healthcare web application designed to enhance accessibility and streamline medical support. It enables users to check symptoms, connect with doctors through virtual consultations, track health data in realtime, and calculate their Body Mass Index (BMI) effortlessly. The platform leverages artificial intelligence to deliver personalized health insights, empowering users to make informed decisions. Secure and encrypted communication ensures that all interactions between patients and healthcare professionals are private and compliant with medical data protection standards. LifeCare features an intelligent symptom checker that offers preliminary health evaluations and recommendations. Users can consult with certified doctors online, helping to reduce unnecessary hospital visits. Advanced AI algorithms predict potential health issues early, promoting timely interventions and preventive care. Additional features include medication reminders, emergency alerts, and tailored health advice. Users can also access detailed information about medications, including their uses and potential warnings. By integrating modern technology and AI, LifeCare transforms traditional healthcare into a more proactive, data-driven, and userfriendly experience—ultimately improving the quality of patient care.